Bilateral Vocal Cord Carcinoma in a Sarcoidosis Patient during Infliximab Therapy - Adriane D. M. Vorselaars; Elisabeth V. Sjögren; Coline H. M. van Moorsel; Jan C. Grutters (Case Reports in Pulmonology)
Introduction. Although the role of TNF-α in tumor development is not fully understood, an increased risk of malignancy with TNF-α-inhibitors, such as infliximab, has been suggested. Case Presentation. We present a 54-year-old nonsmoking female sarcoidosis patient. After seven months of infliximab therapy a T1aN0M0 larynx carcinoma of the right vocal cord was found and excised. Within a year, whilst still on treatment, a second larynx carcinoma of the opposite vocal cord appeared. Discussion. A bilateral vocal cord tumor is rare, especially in a never smoker. Evidence on the role of infliximab in carcinogenesis is inconclusive. To date, there are no follow-up studies evaluating malignancy risk of infliximab therapy in sarcoidosis patients. No studies in other diseases focus on laryngeal carcinomas during infliximab use. We argue that infliximab treatment might have attributed to the rapid progression of vocal cord carcinomas in this patient with an a priori low risk tumor profile. This case illustrates that caution remains warranted in patients with previous malignancies when considering initiation of TNF-α-inhibitors.